Предмет: Алгебра,
автор: yeahboiii
Помогите решить
(8+3√2)*(8-√18)
(√7-√5)*(√63+3√5)
Ответы
Автор ответа:
1
(8+3√2)*(8-√18) = (8+3√2)*(8-3√2) = 64 - 18 = 46
(√7-√5)*(√63+3√5) = (√7-√5)*(3√7+3√5) = 3(√7-√5)*(√7+√5) = 3(7 - 5) = 6
Автор ответа:
1
√18=3√2
(8+3√2)(8-3√2)=64-18=46
√63=3√7
(√7-√5)*3(√7+√5)=3(7-5)=6
(8+3√2)(8-3√2)=64-18=46
√63=3√7
(√7-√5)*3(√7+√5)=3(7-5)=6
Похожие вопросы
Предмет: Физика,
автор: ebanashkaaa
Предмет: Математика,
автор: argenotorov312
Предмет: Геометрия,
автор: yusupihjumarzhan
Предмет: Математика,
автор: vikakovaleva78